Green Synthesis of Five-Membered Hetarene N-Oxides: A Designed Approach to the Synthesis of Substituted Chromeno[3,4-c]pyrrole-2-oxides - Alizadeh, Abdolali; Rostampoor, Azar; Hasanpour, Hamidreza (Synthesis, 2023)
An efficient and chemoselective synthesis of biologically valuable chromeno[3,4-c]pyrrole 2-oxides containing one chiral stereocenter is described. In this method, by using a sequential nucleophilic addition reaction involving coumarins (α,β-unsaturated coumarins or 3-acetylcoumarins), activated acetylenic compounds, triphenylphosphine as a catalyst, and hydroxylammonium chloride (HAC) as an NO source, substituted chromeno[3,4-c]pyrrole 2-oxides were prepared with excellent efficiency. Readily available starting materials, absence of a metal catalyst, green and mild conditions, chemoselectivity, easy purification (the products can be purified by simple filtration and washing with EtOH), and synthetically useful yields are some highlighted advantages of this unprecedented transformation.
Keywords: coumarin; triphenylphosphine; hydroxylammonium chloride; proton transfer process; intramolecular cycloaddition; five-membered hetarene N-oxides